Study on the Adsorption Performance and Adsorption Mechanism of Graphene Oxide by Red Sandstone in Aqueous Solution - Na Li; WenHao Dai; HaiBo Kang; Beifeng Lv; Ping Jiang; Wei Wang (Adsorption Science & Technology)
In order to deal with the increasingly serious pollution of graphene oxide (GO) to the environment. In this paper, the use of red sandstone to treat GO-contaminated aqueous solution is proposed for the first time, and the adsorption capacity and adsorption mechanism of red sandstone to GO are discussed. The controlled variable method was used to explore the optimal pH, concentration, and quality of red sandstone for GO aqueous solution. The adsorption isotherm, thermodynamics, and adsorption kinetics were fitted. Adsorption characterization tests were performed using XRD, AFM, XPS, FT-IR, SAP, TEM, SAP, laser particle size analyzer, and SEM. The results show that when T=303 K, the optimum adsorption condition of red sandstone for GO is pH=4, the mass of the adsorbent is 40 mg, and when the concentration of GO is 80 mg/L, the adsorption capacity is 90 mg/g. The adsorption isotherm model fits the Langmuir model. The adsorption thermodynamic experiments and fitting results show that the reaction is endothermic. XRD and FT-IR tests showed that CaCO3 in red sandstone was involved in the adsorption of GO. SEM, TEM, and AFM microscopic results showed that GO was adsorbed on the surface of red sandstone particles. The XPS test showed that Ca2+ in red sandstone and C=O bond in GO undergo ionic or coordination reaction. The adsorption kinetics fit a pseudo-second-order kinetic model. This study will provide some references for the removal of GO in the environment and the interaction mechanism with natural minerals.